2017
DOI: 10.1038/tp.2017.200
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted cortical brain network in post-traumatic stress disorder patients: a resting-state electroencephalographic study

Abstract: This study aimed to examine the source-level cortical brain networks of post-traumatic stress disorder (PTSD) based on the graph theory using electroencephalography (EEG). Sixty-six cortical source signals were estimated from 78 PTSD and 58 healthy controls (HCs) of resting-state EEG. Four global indices (strength, clustering coefficient (CC), path length (PL) and efficiency) and one nodal index (CC) were evaluated in six frequency bands (delta, theta, alpha, low beta, high beta and gamma). PTSD showed decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 72 publications
(59 reference statements)
1
25
0
1
Order By: Relevance
“…Gross artifacts, such as movement artifacts, were rejected by visual inspection by a skilled expert. After rejecting artifacts, the data were bandpass filtered at 1−55 Hz and segmented into epochs with a duration of 4.096 s. The epochs were rejected if they contained significant physiological artifacts (amplitude exceeding ±75 μV) at any site over all electrodes, and ten artifact-free epochs were used for each subject for source-level network analysis ( Shim et al, 2017 ). Epoch length was determined considering both efficiency and reliability based on previous research findings ( Gudmundsson et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gross artifacts, such as movement artifacts, were rejected by visual inspection by a skilled expert. After rejecting artifacts, the data were bandpass filtered at 1−55 Hz and segmented into epochs with a duration of 4.096 s. The epochs were rejected if they contained significant physiological artifacts (amplitude exceeding ±75 μV) at any site over all electrodes, and ten artifact-free epochs were used for each subject for source-level network analysis ( Shim et al, 2017 ). Epoch length was determined considering both efficiency and reliability based on previous research findings ( Gudmundsson et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some functional magnetic resonance imaging (fMRI) studies have shown an altered resting-state FC in some brain regions, including the amygdala, anterior cingulate cortex (ACC), and medial prefrontal cortex in patients with PTSD, as compared to healthy controls [84,85]. These findings suggest that disrupted frontal network connectivity may be related to those who struggled to recover from adverse experiences [86].…”
Section: The Role Of the Prefrontal Cortex In Cognitive Control Emotmentioning
confidence: 99%
“…Moreover, from a brain-network-organization perspective, the reorganization of brain networks and their association with adverse experiences may serve as an important predictive marker for normal functioning [117]. Some people experience higher levels of severe adversity; this can disrupt the brain network [86] and weaken the cognitive flexibility needed to adjust negative emotions back to their normal affective state. Worse still, an adverse event can lead to a large surprise that may impair the cognition-emotion processing and amplify larger switching costs for cognitive flexibility.…”
Section: Linking the Malleable Brain Resilient Mind And Adaptive Bementioning
confidence: 99%
“…Connectome‐based analyses to characterize specific topological properties of whole‐brain connectivity (Bullmore & Sporns, 2009) report mostly inconsistent results, with limited evidence of topological alterations in individuals with PTSD (Lei et al, 2015; Long et al, 2013; Niu et al, 2018; Shim, Im, & Lee, 2017; Spielberg, McGlinchey, Milberg, & Salat, 2015; Suo et al, 2015; Xu et al, 2018; H. Zhu et al, 2019). The primary findings thus far suggest that individuals with PTSD have greater “small‐worldness” (i.e., more clustering and shorter connections [“paths”] that link regions within the network) and greater centrality (i.e., more central regions [“nodes”] with a high number of paths passing through them) in DMN and SN, further highlighting the roles of these networks in PTSD (Lei et al, 2015; Long et al, 2013).…”
Section: Introductionmentioning
confidence: 99%